2020
DOI: 10.3390/ijms21186524
|View full text |Cite
|
Sign up to set email alerts
|

Electroacupuncture Modulates Spinal BDNF/TrκB Signaling Pathway and Ameliorates the Sensitization of Dorsal Horn WDR Neurons in Spared Nerve Injury Rats

Abstract: Neuropathic pain is more complex and severely affects the quality of patients’ life. However, the therapeutic strategy for neuropathic pain in the clinic is still limited. Previously we have reported that electroacupuncture (EA) has an attenuating effect on neuropathic pain induced by spared nerve injury (SNI), but its potential mechanisms remain to be further elucidated. In this study, we designed to determine whether BDNF/TrκB signaling cascade in the spinal cord is involved in the inhibitory effect of 2 Hz … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 60 publications
(106 reference statements)
2
19
0
Order By: Relevance
“…It was demonstrated that noxious and non-noxious stimuli elicited a progressive increase of WDR neurons response along with the increasing of stimulation intensity. The present study demonstrated that the analgesic effect of EA-Ta may be involved in the inhibition of WDR neurons in the spinal dorsal horn, which is consistent with previous reports ( Yu et al, 2019 ; Wang et al, 2020 ; Xue et al, 2020 ).…”
Section: Discussionsupporting
confidence: 94%
“…It was demonstrated that noxious and non-noxious stimuli elicited a progressive increase of WDR neurons response along with the increasing of stimulation intensity. The present study demonstrated that the analgesic effect of EA-Ta may be involved in the inhibition of WDR neurons in the spinal dorsal horn, which is consistent with previous reports ( Yu et al, 2019 ; Wang et al, 2020 ; Xue et al, 2020 ).…”
Section: Discussionsupporting
confidence: 94%
“…During the process of acupuncture-induced analgesia, signals are transferred from acupoints to the CNS, resulting in the spinal cord and brain to release neurotransmitters and neuromodulators (such as opioids, serotonin, and norepinephrine) to suppress pain [ 4 , 35 ]. Some studies revealed that EA can ameliorate neuropathic pain by inhibiting the activation of microglia and upregulating of BDNF expression in the CCI model [ 9 , 36 ], which is similar to the results of this study. Moreover, BDNF participates in the formation of spinal cord central sensitization by mediating LTP [ 33 ] and is related to synaptic remodelling [ 13 , 15 ].…”
Section: Discussionsupporting
confidence: 91%
“…Consistently, a decrease in BDNF levels has been reported in neurodegenerative disorders, such as AD [ 69 , 71 ], Huntington’s disease (HD) [ 72 ], and epilepsy [ 73 ], and recent strategies aimed at sustaining or even amplifying the production of BDNF have been proved to be beneficial in patients with HD [ 74 ], AD [ 75 , 76 ], Parkinson’s disease (PD) [ 77 , 78 ], amyotrophic lateral sclerosis (ALS) [ 79 , 80 , 81 ], stroke [ 82 , 83 , 84 ], and spinal cord injury [ 85 , 86 , 87 , 88 ]. However, it is worth mentioning that despite the extensive literature dating back to the early 1990s, in which reduced BDNF levels in the brain have been associated with neurodegenerative diseases, only in patients with HD has a genetic defect in BDNF gene been mechanistically related to the pathology [ 89 ].…”
Section: Bdnf In Health and Diseasementioning
confidence: 99%